HIV testing for acute medical admissions: evaluation of a pilot study in Leicester, England. Issue 4 (7th November 2012) - Palfreeman, Adrian; Nyatsanza, Farai; Farn, Helen; McKinnon, Graham; Schober, Paul; McNally, Paul
Abstract : Objectives: The 2008 UK National Guidelines for HIV testing recommended HIV testing should be offered to all general medical admissions aged 16–60 years in high prevalence areas, and that this should be evaluated to ensure this was effective in diagnosing previously undiagnosed HIV. Methods: HIV testing was introduced as a routine test for all patients admitted to the acute medical admissions unit, comparisons were made between the testing rates before, during and after this intervention. Results: The pilot was initiated in August 2009. Prior to the pilot the unit was carrying out 15 tests per month. However, when the pilot was introduced 82 tests were being carried out per month with a total of 10 new diagnoses since the start of the pilot. The proportion of patients tested versus those eligible for testing remained low varying between 6% and 22% month by month. 10 patients we found to be HIV positive with a prevalence of approximately 1%, 10 fold higher than the cut off for cost effectiveness used in the guidelines. Conclusions: Overall the pilot showed that HIV testing could be delivered without the use of extra resources and is acceptable to patients.